Model Ideal Sistem Manajemen Rantai Pasok Agribisnis Kakao: Pendekatan Soft System Methodology (SSM) - Rahaditya Dimas Prihadianto; Yuli Hariyati; Indah Ibanah; Kamil Muhtadi; Sony Suwasono; Djoko Sumarno (JSEP (Journal of Social and Agricultural Economics), 2022)
Jambewangi village cocoa farmers market their cocoa beans individually and in small quantities, so they’re in a low bargaining position. In addition to not optimally the role of each institution, they also haven’t coordinated and cooperated to promote cocoa. Researchers need to research to design institutional synergies in the agribusiness supply chain. The research was conducted in Jambewangi villages, the center of cocoa production in Banyuwangi. The supply chain design is based Soft System Methodology (SSM) approach through information from sources, farmers, and experts. Based on the SSM analysis, it can be concluded that: 1. There is a fundamental problem with the cocoa in Jambewangi village that farmers only produce unfermented cocoa beans, and sell them individually, so their bargaining position is low. Several institutions in the village haven’t played an optimal role in joint marketing, 2. There is no synergy between institutions at the farmer level, so they can’t protect farmers in their bargaining position. 3. If supply chain actors synergize and carry out their respective roles in the supply chain, uniform, and SNI-standardized cocoa beans can be produced and are able to produce processed chocolate products such as butter, chocolate bars, and powder.